2006
DOI: 10.1068/p5487
|View full text |Cite
|
Sign up to set email alerts
|

Grouping and Trajectory Storage in Multiple Object Tracking: Impairments Due to Common Item Motions

Abstract: In our natural viewing, we notice that objects change their locations across space and time. However, there has been relatively little consideration of the role of motion information in the construction and maintenance of object representations. We investigated this question in the context of the multiple object tracking (MOT) paradigm, wherein observers must keep track of target objects as they move randomly amid featurally identical distractors. In three experiments, we observed impairments in tracking abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
(29 reference statements)
0
30
0
1
Order By: Relevance
“…Consequently, these results suggest that individual differences in tracking performance may be primarily determined by how efficiently the visual system can individuate the targets from one another as well as from the distractors (Sears and Pylyshyn, 2000;Intriligator and Cavanagh, 2001;Ogawa et al, 2002;Vogel et al, 2005;Suganuma and Yokosawa, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Consequently, these results suggest that individual differences in tracking performance may be primarily determined by how efficiently the visual system can individuate the targets from one another as well as from the distractors (Sears and Pylyshyn, 2000;Intriligator and Cavanagh, 2001;Ogawa et al, 2002;Vogel et al, 2005;Suganuma and Yokosawa, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, we believe it unlikely that the lack of an interaction was due to the range of speeds or distances used. In this experiment, tracking might have been affected not only by spatial proximity, but also by temporal proximity (Verstraten et al, 2000) and similarity of motion (Suganuma & Yokosawa, 2006) of the targets and distractors, which may have been increased in the near distance condition. Previous studies have shown that MOT performance declines as the number of distractors increases (Bettencourt & Somers, 2009;Feria, 2012;Sears & Pylyshyn, 2000;Tombu & Seiffert, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Object files may store various visual and spatial features of objects, such as colour, orientation, and location (Treisman, 2006). In contrast, indices only select and refer to individual objects (Pylyshyn, 2007)*although some writers have proposed that in some cases there may be a compulsory encoding of location in the associated object files (Fencsik, Klieger, & Horowitz, 2007;Keane & Pylyshyn, 2006;Suganuma & Yokosawa, 2006). But perceptual information does not appear to be routinely encoded.…”
mentioning
confidence: 96%